Methionine synthase A2756G polymorphism may predict ulcerative colitis and methylenetetrahydrofolate reductase C677T pancolitis, in Central China - Bronowicki Jean-Pierre; Guéant-Rodrigue; Xia Bing; Peyrin-Biroulet Laurent; Chen Min; Bigard Marc-André; Guéant Jean-Louis (BMC, 2008)
Abstract Background The association of genetic polymorphisms related to metabolism of homocysteine with inflammatory bowel disease has been evidenced in Crohn disease and remains an open question in ulcerative colitis. We evaluated the association of the polymorphisms of MTHFR, MTR, MTRR and TCN2 genes with ulcerative colitis in Central China. Methods 168 patients were genotyped for these polymorphisms and compared to 219 matched controls. Results Methionine synthase 2756G allele frequency was higher in ulcerative colitis than in controls 0.15 (95% C.I. 0.11-0.19) vs 0.09 (95% C.I. 0.07 - 0.12), (P = 0.0137) and predicted ulcerative colitis risk in logistic regression, with an Odds ratio at 1.8 (95% C.I. 1.15-2.84). Methylenetetrahydrofolate reductase 677TT genotype was 2.7-fold more prevalent in individuals with pancolitis than in those with left colitis or proctitis, with respective percentages of 27.3 (95% C.I.16.4-42.0) and 10.5 (95% C.I. 6.3-17.1) (P = 0.0123). The carriage of 677TT or 677CT/1298AC genotypes of methylenetetrahydrofolate reductase was more frequent in cases with pancolitis than in subjects with left colitis or proctitis (P = 0.0048), with an Odds ratio adjusted by age and sex at 3.3 (95% C.I. 1.4-7.9), P = 0.0084) in logistic regression. Conclusion Methionine synthase and methylenetetrahydrofolate reductase are genes of vitamin B12 and folate cellular metabolism associated respectively with risk and extent of ulcerative colitis, at least in Central China. This finding may open new insights, particularly for the potential interest in treating patients carrying the 677TT MTHFR genetic trait and a deficit in folate.